Faktor Keterlibatan Remaja Terhadap Pesta Minuman Keras dan Narkoba: Analisis Pemberitaan Kasus Indramayu - Paramesti, Nirwasita Zada; Syahrani, Devy Fitri; Sifana, Firdha; Zalifah, Yearta Kurnia; Maharany, Chezia; Az’zahra M. D. W, Inge Nur; Primananda, Muhammad Athaya; Alamsyah, Fiqih Dien; Syalsabila, Khairunisa; Rachma, Aqila Aulia; Anisah, Aura; S, Subakdi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The phenomenon of alcohol and drug abuse among teenagers and young people in Indonesia continues to show a worrying trend, both in terms of the level of occurrence and the consequences caused. This article aims to reveal the main factors driving the occurrence of drinking parties that lead to drug abuse among young people and relevant prevention and handling strategies, in order to reduce the risk of similar incidents in the future. This study uses a qualitative approach with content analysis obtained from news broadcasts and media documentation. The results of this study indicate that adolescent involvement in drinking parties is driven by internal factors such as curiosity and the search for identity, as well as external factors such as peer pressure and permissive social norms, and the transition to drug abuse occurs gradually and is reinforced by interactions in the community. In terms of handling, the legal approach is now starting to prioritize rehabilitation over criminalization, although challenges such as lack of facilities and community stigma are still obstacles in the process of social reintegration. Therefore, a collaborative approach is needed involving families, schools, communities, and law enforcement.